How can we increase the (perceived) benefit of exercise classes to the students? - Wilhelm, Matthias (Improving University Science Teaching and Learning, 2023)
In the physics curriculum at the University of Copenhagen, a considerable amount of time of the teachers and teaching assistants (TAs) is spent on exercise classes. Likewise, the students are expected to spend considerable time on them. Naturally, this time should be spent efficiently, to the best possible benefit of the students, to achieve the highest possible learning outcome. At the same time, the students also have to perceive the exercise classes as beneficial, since otherwise they do not show up and thus do not benefit (or are not motivated to actively participate, and thus benefit less). The possible difference between perceived and actual benefit is of course partially a question of constructive alignment (Biggs, 1996; John & Catherine, 2003) and congruence (McCune & Hounsell, 2005).